Biomimetic spray coating for fruit preservation based on UiO-1 67 metal–organic framework nanozyme - Li, Jie; Wang, Donglin; Liu, Yuhang (Frontiers in Materials, 2024)
The application of edible coatings for preparing composite antibacterial spray coatings for fruit preservation by incorporating antibacterial nanoparticles has gained increasing attention. Chitosan (CS) is a natural polysaccharide used as an edible coating to preserve fruit; it has properties such as reducing water loss, enhancing appearance, and improving mechanical properties. By combining it with antibacterial material, it can reduce fruit microorganisms. Cerium (Ce) has excellent antibacterial activity combined with the advantages of safety and low cost. Therefore, this study proposes a biocatalytic spray coating for fruit preservation using a CS composite metal–organic framework (CS@Ce-MOF) with strawberry as a model fruit. CS@Ce-MOFs are superior to Ce-MOFs in the aqueous stability of their chemical structure, inoxidizability, antibacterial duration, and validity. The well-characterized CS@Ce-MOF was verified to simultaneously mimic good oxidase- and apyrase-like activities. CS@Ce-MOF biocatalytic spray coating demonstrated excellent antibacterial properties against two common foodborne pathogens: Escherichia coli and the Gram-positive bacterium Staphylococcus aureus, with high killing rates of up to 94.5%. This is due to the unique structure of the CS@Ce-MOF composite, which presents a large surface area for contact with pathogens and enhances the catalytic activity of the incorporated cerium oxide nanoparticles, leading to efficient sterilization. Furthermore, the scavenging rate of DPPH and ABTS free radicals is more than 80%, indicating that CS@Ce-MOF has excellent antioxidant properties. Moreover, CS@Ce-MOF minimized the weight loss and firmness of strawberries and bananas over 7 days of ambient storage. The use of such a biocatalytic spray coating has enormous potential for preserving the quality and safety of fresh produce, reducing food waste, and promoting sustainable agricultural practices.